Symmetrical Neurons and the development of empathy against aggression and conflict in the school - Rosa Isabel Galvis (Corporación Universitaria Minuto de Dios, 2015)
This work aimed at studying and theoretical analysis of empathy, its development and role in the processes of social interaction, in order to clarify aspects of neurobiological, psychosocial and cultural nature that may affect the formation processes. So far, we have found that empathy is one of the psychosocial aspects that play an important role in the resolution of conflict and aggression within the school environment. Therefore, this is a reflection on the various aspects of theoretical and methodological problems that contribute to strengthen and allow formation of empathetic and sensitive individuals that can feel the pain of others. This could be viewed as an alternative to deal with the actual and constant conflict and aggression present in school environments, and thus motivate a future design of potential pedagogical alternatives that would address this problem.